2012
DOI: 10.1142/s1793830912500474
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor Sum Distinguishing Coloring of Some Graphs

Abstract: A proper [k]-edge coloring of a graph G is a proper edge coloring of G using colors of the set [k] = {1, 2,…,k}. A neighbor sum distinguishing [k]-edge coloring of G is a proper [k]-edge coloring of G such that for each edge uv ∈ E(G), the sum of colors taken on the edges incident to u is different from the sum of colors taken on the edges incident to v. By ndiΣ(G), we denote the smallest value k in such a coloring of G. In this paper, we obtain that (1) ndiΣ(G) ≤ max {2Δ(G) + 1, 25} if G is a planar graph, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In particular it implies that χfalse(Gfalse)Δfalse(Gfalse)+13 for every planar graph G without an isolated edge. Independently, planar graphs were also investigated in and , where the bounds χ(G)trueprefixmax{2normalΔ(G) +1,25} and χfalse(Gfalse)max{normalΔ(G)+10,25}, resp., were proved for these graphs. See also for other results concerning χfalse(Gfalse).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular it implies that χfalse(Gfalse)Δfalse(Gfalse)+13 for every planar graph G without an isolated edge. Independently, planar graphs were also investigated in and , where the bounds χ(G)trueprefixmax{2normalΔ(G) +1,25} and χfalse(Gfalse)max{normalΔ(G)+10,25}, resp., were proved for these graphs. See also for other results concerning χfalse(Gfalse).…”
Section: Introductionmentioning
confidence: 99%
“…Independently, planar graphs were also investigated in and , where the bounds χ(G)trueprefixmax{2normalΔ(G) +1,25} and χfalse(Gfalse)max{normalΔ(G)+10,25}, resp., were proved for these graphs. See also for other results concerning χfalse(Gfalse). The main result of this article, see Theorem , not only implies that Conjecture is valid for planar graphs of maximum degree at least 28, but also strengthens it by assuring sufficiency of an upper bound from Vizing's theorem to hold within our much more restrictive setting, that is, we prove that χfalse(Gfalse)Δfalse(Gfalse)+1 for these graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Then ndi Σ (G) ≤ ∆(G) + 3col(G) − 4. Theorem 1.7 (Dong and Wang [5]). Let G be a normal planar graph.…”
Section: Conjecture 12mentioning
confidence: 99%
“…Dong et al [12] considered the neighbor sum distinguishing colorings of planar graphs and showed that if G is a normal planar graph, then ndi (G) ≤ max{2 (G) + 1, 25}. In [13], Dong et al proved that if G is a normal graph and mad(G) ≤ 5/2, then ndi (G) ≤ k where k = max{ (G) + 1, 6}.…”
Section: Conjecture 11 [2]mentioning
confidence: 99%